Recent Advances in CFD for Wind and Tidal Offshore Turbines - Ferrer, Esteban; Montlaur, Adeline (Springer Tracts in Mechanical Engineering, 2019)
The book presents novel Computational Fluid Dynamics (CFD) techniques to compute offshore wind and tidal applications. The papers in this volume are based on a mini-symposium held at ECCOMAS 2018. Computational fluid dynamics (CFD) techniques are regarded as the main design tool to explore the new engineering challenges presented by offshore wind and tidal turbines for energy generation. The difficulty and costs of undertaking experimental tests in offshore environments have increased the interest in CFD which is used to design appropriate turbines and blades, understand fluid flow physical phenomena associated with offshore environments, predict power production or characterise offshore environments amongst other topics.